Smartphone Digital Image Colorimetry Combined with Dispersive Solid-Phase Microextraction for the Determination of Quercetin in Food Samples - Ismail, Salihu; Alshana, Usama; Al-Hashemi, Shareef; Zaman, Buse Tugba; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2026)
Smartphone digital image colorimetry, combined with dispersive solid-phase microextraction, is reported for the determination of quercetin. Optimum detection conditions were achieved using a wavelength of 485 nm, a distance of 8.0 cm to the detection camera with 10.0% background brightness, and an area of interest of 125.0 px2. Optimum extraction conditions were found as a sample solution pH of 5.50 with a quercetin-to-aluminum mole ratio of 1:1 within 60 s. Zirconium nanoparticles (40.0 mg) and nitric acid (100 mu L, 1.5 mol L-1 in acetone) were used as the adsorbent and eluent, respectively. The method's limits of detection and quantitation were found as 0.03 and 0.11 mu g mL-1, respectively. Coefficients of determination (R2) were higher than 0.9954, and the relative standard deviations were lower than 8.5%. The proposed method was applied for the determination of quercetin in fruit and vegetable samples with recoveries ranging from 93.0 to 108%.
Keywords: Digital image colorimetry; dispersive solid-phase microextraction; food analysis; quercetin; smartphone; GRAPHENE OXIDE; ANTIOXIDANT; FRUITS; Chemistry